Management of the Utilisation of Dasa Wisma Estates as a Living Pharmacy in Nagari Batang Arah Tapan, Basa Ampek Balai Tapan District: Manajemen Pemanfaatan Perkarangan Dasa Wisma Sebagai Apotik Hidup Di Nagari Batang Arah Tapan Kecamatan Basa Ampek Balai Tapan - Aulan Tilfasari; Ahmad Khairul Nuzuli; Winda Oktaviana (Institute of Educational, Research, and Community Service, 2023)
This research aims to examine the management of utilizing the Dasa Wisma yard as a living pharmacy in Nagari Batang Arah Tapan, Basa Ampek Balai Tapan Subdistrict. The study employs a qualitative approach. Data collection is conducted through several stages, namely field observation, interviews, and documentation. After collecting the data, a structured data analysis is carried out, which involves qualitative analysis of the data obtained from interviews and field observations. The results of this research indicate that this approach successfully enhances the community's understanding of the benefits of medicinal plants, contributes positively to the economic and health sectors, and receives positive responses from the community. The selected types of medicinal plants, such as ginger, turmeric, galangal, and aromatic ginger, have clearly identified benefits and are processed into traditional remedies. In conclusion, the management of utilizing the Dasa Wisma yard as a living pharmacy provides significant benefits in the sustainable development of natural resources and environmental values education. Thus, this research emphasizes the importance of harmony between local knowledge and modern innovation in creating a healthy and sustainable environment in Nagari Batang Arah Tapan